The implementation of maintenance system in Malaysia’s public housing at Kota Bharu, Kelantan - Nurhidayah, Azmy; Ahmad-Nazri, Elly HF; Liyana, Mohamed Yusof; Gad, Ghada M. (Penerbit UTHM, 2023)
Establishing an effective maintenance system in public housing buildings is essential in ensuring the building operates optimally and enhances residents' satisfaction. However, the maintenance management in Malaysian public housing is considered low, particularly on leaky roofs, dysfunctional elevators and obstructed pipes. Consequently, the deterioration of facilities and services makes the residents dissatisfied. Consequently, the study aims to determine the current implementation and effectiveness of the maintenance system for public housing by focusing on the residents' satisfaction level and the practice of the maintenance personnel. Surveys were conducted with residents and maintenance personnel from the Projek Perumahan Rakyat Kota Bharu's public housing. A total of 230 questionnaires were considered valid and analyzed to rank the residents' satisfaction level towards public housing maintenance and the practice of the maintenance personnel in public residential buildings. The data was analyzed using the Mean Analysis in the Statistical Package for Social Science (SPSS). The result revealed that the residents are satisfied with the maintenance system's performance, with an electrical system as the most satisfying maintenance performance rated by the residents, compared with other aspects of the maintenance performance factors, with a mean score of 3.94. However, several aspects of the maintenance system, namely cleaning services, security system, and time for repairing the defects, still need improvement to enhance the maintenance quality of public housing in Malaysia.